Vascular endothelial growth factor (VEGF) and prostate pathology - Botelho,Francisco (2010)
PURPOSE: Previous studies suggest that vascular endothelial growth factor (VEGF) circulating levels might improve identification of patients with prostate cancer but results are conflicting. Our aim was to compare serum VEGF levels across different prostate pathologies (including benign prostatic hyperplasia, prostatitis, high grade prostate intraepithelial neoplasia and prostate cancer) in patients at high risk of prostate cancer. MATERIALS AND METHODS: We consecutively enrolled 186 subjects with abnormal digital rectal examination and/or total PSA (tPSA) = 2.5 ng/mL. Blood was collected before diagnostic ultrasound guided trans-rectal prostate biopsy, or any prostate oncology treatment, to measure PSA isoforms and VEGF. Unconditional logistic regression was used to compute age-, tPSA- and free/total PSA-adjusted odds ratios (OR) and respective 95% confidence intervals (95% CI) for the association between serum VEGF and different prostatic pathologies. RESULTS: Prostate biopsy main diagnoses were normal or benign prostatic hyperplasia (27.3%), prostatitis (16.6%), and prostatic cancer (55.0%). The median VEGF levels (ng/mL) in these groups were 178.2, 261.3 and 266.4 (p = 0.029), respectively, but no significant differences were observed for benign vs. malignant pathologies (215.2 vs. 266.4, p = 0.551). No independent association was observed between VEGF (3rd vs. 1st third) and prostate cancer, when compared to benign conditions (adjusted OR = 1.44; CI 95%: 0.64-3.26). CONCLUSIONS: In patients at high risk of prostate cancer, circulating VEGF levels have no clinical role in deciding which patients should be submitted to prostate biopsy. Prostatitis patients, often with higher PSA levels, also present high serum levels of VEGF, and their inclusion in control groups might explain the heterogeneous results in previous studies.